2015
DOI: 10.1063/1.4916403
|View full text |Cite
|
Sign up to set email alerts
|

Full-range electrical characteristics of WS2 transistors

Abstract: Transistors with chemically synthesized layered semiconductor WS2 exhibiting 105 room temperature modulation and ambipolar behavior We fabricated transistors formed by few layers to bulk single crystal WS 2 to quantify the factors governing charge transport. We established a capacitor network to analyze the full-range electrical characteristics of the channel, highlighting the role of quantum capacitance and interface trap density. We find that the transfer characteristics are mainly determined by the interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…MoTe 2 has shown similar electrical properties to other TMDCs including the highly utilized MoS 2 . [8][9][10][11][12][13] In few-layer MoTe 2 the band gap is in the range 1-1.1 eV, extending to near infrared the range of band gaps available for TMDCs. [14] The photoconductivity of MoS 2 has been well researched, [6,7,[15][16][17][18][19][20] however MoTe 2 has only just begun to be explored for its optoelectronic properties and MoTe 2 flakes of thicknesses in the one to four layer range have not previously been studied optoelectronically.…”
Section: Communicationmentioning
confidence: 99%
“…MoTe 2 has shown similar electrical properties to other TMDCs including the highly utilized MoS 2 . [8][9][10][11][12][13] In few-layer MoTe 2 the band gap is in the range 1-1.1 eV, extending to near infrared the range of band gaps available for TMDCs. [14] The photoconductivity of MoS 2 has been well researched, [6,7,[15][16][17][18][19][20] however MoTe 2 has only just begun to be explored for its optoelectronic properties and MoTe 2 flakes of thicknesses in the one to four layer range have not previously been studied optoelectronically.…”
Section: Communicationmentioning
confidence: 99%
“…The direct bandgap in black phosphorus is dependent on the number of layers, ranging from about 0.3 eV in bulk (5 or more layers) [3] to about 2 eV for a single layer [4]. In contrast to other two-dimensional materials, where the mobility is commonly far below that of graphene [5,6,7], the mobility in black phosphorus can approach values on the order of 10,000 cm 2 V -1 s -1 [1]. The presence of a direct band gap along with the high carrier mobility makes black phosphorus an interesting candidate for fast field-effect transistors [8] and optoelectronic devices like photodetectors [9,10].…”
mentioning
confidence: 99%
“…This results indicated that the intrinsic carrier mobility on the SiO 2 substrate is significantly greater than the values previously reported in MoS 2 FETs [42]. The analogous configuration also applied to FETs based on MoS 2 [52], MoSe 2 [55], MoTe 2 [59], WS 2 [68], and WSe 2 [40]. Therefore, future studies of TMDCs devices should use the four-terminal measurement.…”
Section: Figure 1 (A) a Mos2 Thin Film Transistor And Its Transport mentioning
confidence: 59%